Which stream wood becomes functional following wildfires? - Vaz, Pedro (2014)
Large wood is a critical element in stream ecosystems, but only a subset of wood pieces actually provide hydraulic, geomorphic, and ecological functions. We test the current paradigm that larger pieces provide more function, and examine the role wildfires may play in affecting functionality of recruited wood. We conducted a cross-basin analysis in nine central Portugal watersheds, obtaining a variety of measurements on 1483 wood pieces (diameter ≥ 0.05 m; length ≥ 0.5 m) in 27 streams burned within six years prior. We examined nonlinear relationships and indirect effects on function using Generalized Additive Modeling and Structural Equation Modeling. Variables with direct effects on function were piece diameter, rootwads, anchoring, position (bridging, ramping, loose), longitudinal distance along the stream continuum, and the ratio of piece length to channel width. The effect of length ratio on function was nonlinear. Relatively long pieces were more likely to be functional until they were ∼3 times the channel width, at which point longer pieces became less likely to be functional. Post-fire wood likely lacked complexity and longer pieces were more likely to be bridging; both conditions may have prohibited them from interacting with the wetted area. Wildfires had indirect effects on function. Burned pieces were more likely to be large in diameter (thus more likely functional) but not anchored (thus less likely functional); these antagonistic effects may be the reason burned status had no direct effect on function. Our results challenge the wellestablished idea that the function of wood in streams is simply a matter of wood size, along with indicators of longevity (e.g. stability and decay status). Relatively long pieces may in fact provide less function to the stream, at least until they break or are transported further downstream. Practitioners installing wood to streams should consider pieces with wide diameter and rootwads, approximately 3 times the channel width, and anchored but not bridging the channel.